2021
DOI: 10.1002/adhm.202002227
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ligand Density and Degradability on Hydrogel Induced Breast Cancer Dormancy and Reactivation

Abstract: The role of hydrogel properties in regulating the phenotype of triple negative metastatic breast cancer is investigated using four cell lines: the MDA-MB-231 parental line and three organotropic sublines BoM-1833 (bone-tropic), LM2-4175 (lung-tropic), and BrM2a-831 (brain-tropic). Each line is encapsulated and cultured for 15 days in three poly(ethylene glycol) (PEG)-based hydrogel formulations composed of proteolytically degradable PEG, integrin-ligating RGDS, and the non-degradable crosslinker N-vinyl pyrrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 80 publications
(165 reference statements)
2
30
0
Order By: Relevance
“…This protocol has been widely used to detect proliferating cells. [ 16,22,24 ] Similar trend was noticed as observed in Ki67 staining data. The percentage of EdU‐positive cells were significantly higher in spheroids in suspension culture compared to the HA hydrogel (Figure S3, Supporting Information).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This protocol has been widely used to detect proliferating cells. [ 16,22,24 ] Similar trend was noticed as observed in Ki67 staining data. The percentage of EdU‐positive cells were significantly higher in spheroids in suspension culture compared to the HA hydrogel (Figure S3, Supporting Information).…”
Section: Resultssupporting
confidence: 82%
“…However, biomimetic biomaterial scaffolds provide an important tool to study tumor cell–matrix interactions in vitro and thus have been employed as an experimental model to investigate the role of ECM derived cues on cellular dormancy in both the primary [ 18–23 ] and metastatic tumor setting. [ 15,16,24,25 ] In the context of BMBC, very limited experimental models have been reported to investigate the role of ECM derived cues on dormancy. [ 15,16,24 ] Moreover, to the best of our knowledge, none of the studies till date have reported the impact of an ECM mimetic scaffold on the regulation of mass dormancy in both TNBC and HER2+ BMBC spheroids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that in multiple cancers, tumor cells tend to achieve chemotherapeutic resistance by upregulating p‐p38 expression 41–44 . In the context of dormancy, p‐ERK/p‐p38 activity ratio has been studied extensively, where lower activity ratio (<1) is indicative of the dormant state and high activity ratio is indicative of the proliferative state 27,45,46 . To identify if p‐ERK and p‐p38 are involved in attaining the dormant state in 80 nM drug treated spheroids, we performed p‐ERK and p‐p38 immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence staining was performed to detect Ki67, p‐ERK, p‐p38, and Cleaved caspase 3, which were differentially expressed between proliferating versus dormant spheroids as described in prior studies 23,26,27 . Briefly, on day 7, spheroids were dissociated into single cells and added to a 96 well plate.…”
Section: Methodsmentioning
confidence: 99%